Training on the Use of Student Worksheet Real Picture Analysis (RPA) Based for Professional Competence of MA Fatihul Ulum Tanggul Jember Teachers - Wicaksono, Iwan; Ibrahim, Mohd Mokhzani; Sutarto, Sutarto; Indrawati, Indrawati; Hariyadi, Slamet; Hariani, Sulifah Aprilyah (Bubungan Tinggi: Jurnal Pengabdian Masyarakat, 2025)
The availability of teaching materials, especially student worksheet used by teachers at MA Fatihul Ulum Jember, has limitations that trigger misunderstanding of materials and concepts. Training activities aim to improve the professional competence of teachers including: RPA-based student worksheet as an alternative learning choice used to increase students' interest in self-directed learning. The training was attended by 38 Subject Teachers, with the approach used during the process of implementing this training, namely the process approach. The training process involved the following stages: the formation of a team; the formulation of goals; the identification of stakeholders; the collection and analysis of needs; the prioritisation of problems; preparation; implementation; mentoring; review; and evaluation. The training increased teachers' professional competence in the development of RPA-based student worksheet, including characteristics, components, strategies and preparation. Therefore, it is expected that teachers will be more trained and competent in developing student worksheet integrated with real picture to improve students' higher-order thinking.